Impact of health education on knowledge, attitude and practices regarding menstruation and menstrual hygiene among school-going adolescent girls in rural Gurugram, Haryana: a school-based interventional study - Deepika Singh; Nitin Panwar (International Journal Of Community Medicine And Public Health, 2026)
Background: Menstrual hygiene management remains a significant public health concern among adolescent girls, particularly in rural settings where misconceptions, stigma, and inadequate resources persist. Health education has been identified as an effective strategy to improve knowledge, attitude, and practices (KAP) related to menstruation. Methods: A school-based interventional study with a single-group pre-test and post-test design was conducted among 300 adolescent girls aged 10-18 years who had attained menarche. Data were collected using a pre-tested structured questionnaire assessing KAP. A structured health education intervention was delivered in two sessions. The post-intervention assessment was conducted 3 months after the intervention. Results: Among 300 participants, the majority belonged to the 13-15 years age group (48.7%) and studied in government schools (60.7%). Awareness about menstruation prior to menarche was reported by 59.3% of participants, with mothers being the primary source of information (37.3%). Regarding practices, 68.7% used sanitary pads, whereas 17.3% relied on old cloth. More than half (56%) did not change absorbents ≥3 times per day. Attitudinal assessment revealed that 66.7% felt uncomfortable discussing menstruation, and 60% considered cessation of menstruation as fortunate. Post-intervention, there was a statistically significant improvement in knowledge, attitude, and practice scores (p